The effect of direct democratic institutions on income redistribution: evidence from Switzerland - Feld, Lars P.; Fischer, Justina A. V.; Kirchgässner, Gebhard (Political economy and public policy series, 2008)
There is an intensive dispute in political economics about the impact of institutions on income redistribution. While the main focus is on comparison between different forms of representative democracy, the influence of direct democracy on redistribution has attracted much less attention. According to theoretical arguments and previous empirical results, government policies of income redistribution are expected to be more in line with median voter preferences in direct than in representative democracies. In this paper, we find that institutions of direct democracy are associated with lower public spending and revenue, particularly lower welfare spending and broad-based income and property (wealth) tax revenue. Moreover, we estimate a model which explains the determinants of redistribution using panel data provided by the Swiss Federal Tax Office from 1981 to 1997 and a cross section of (representative) individual data from 1992. While our results indicate that less public funds are used to redistribute income and actual redistribution is lower, inequality is not reduced to a lesser extent in direct than in representative democracies for a given initial income distribution. This finding might well indicate the presence of efficiency gains in redistribution policies
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments October 2006 erstellt